Дослідження впливу процесу переетерифікування на триацилгліцерольний склад жирової сировини з різним жирнокислотним складом - Ситнік, Наталія Сергіївна; Демидов, Ігор Миколайович; Мазаєва, Вікторія Сергіївна; Голодняк, Володимир Олександрович (НТУ "ХПІ", 2017)
В статье представлено сравнение равновесного триацилглицерольного состава образцов различных масел с полученным после переэтерификации и установлено, что триацилглицерольный состав переэтерифицированного пальмового масла и его фракции – пальмового олеина – в большей степени совпадает с равновесным в сравнении с жидкими растительными маслами (подсолнечное и соевое). С помощью дифференциальной сканирующей калориметрии показаны изменения в составе триацилглицеролов начального и переэтерифицированного пальмового олеина, которые представлены характеристиками пиков плавления и кристаллизации на ДСК-граммах.

The paper presents a comparison of the equilibrium triacylglicerol composition of samples and obtained after interesterification of various oils and found that the triacylglicerol composition of interesterified palm oil and its fractions – palm olein – largely coincides with the equilibrium in comparison with liquid vegetable oils (soybean and sunflower). Using differential scanning calorimetry changes in the initial and triacylglycerols of interesterified palm olein, which presents characteristics of melting and crystallization peaks in the DSC-grams, was shown.
Study of the influence of interesterification process on triacylglicerol structure of raw fat with different fatty acid composition
Keywords: жирні кислоти; пальмова олія; соняшникова олія; концентрація